Heterogeneity of Pseudomonas savastanoi populations infecting Myrtus communis in Sardinia (Italy). (8th July 2013) - Cinelli, T.; Marchi, G.; Cimmino, A.; Marongiu, R.; Evidente, A.; Fiori, M.
<x xml:space="preserve">Abstract</x> Genetic, phenotypic and host range diversity among Pseudomonas savastanoi isolates from Myrtus communis were investigated. Thirty‐one isolates from six Sardinian commercial myrtle orchards and three isolates from plants growing spontaneously on the island of Rhodes (Greece) were compared with reference strains of P. savastanoi from olive, oleander, ash and myrtle. Multilocus sequence analysis (MLSA) indicated the presence of a monomorphic population with a very low level of variability. Conversely, Biolog phenotypic fingerprinting and phytohormone production analyses showed a considerable metabolic diversity, as bacteria obtained from single infected tissue differed more than bacteria obtained from different orchards. When pathogenicity tests were carried out on myrtle plants, different types of symptoms were induced: knots, canker lesions with or without tissue proliferations and, occasionally, wilting of the inoculated twig, a symptom never reported before for P. savastanoi. Comparable symptoms were also observed in the natural environment both on spontaneous and cultivated plants. Moreover, the host range of the myrtle population was heterogeneous and not well defined. Some isolates showed a wide host range whilst others were pathogenic only to their natural host. Overall these findings suggest that the diversity of the P. savastanoi population from myrtle does not depend so much on the locality or the natural host and does not allow the Sardinian and Greek isolates, together with previously characterized myrtle strains, to be ascribed to a known pathovar of P. savastanoi, nor to propose their belonging, as a whole, to a new pathovar.